Evaluasi Kinerja Ruas Jalan Sukabangun II Kota Palembang Menggunakan Metode PKJI 2023: Performance Evaluation Of Sukabangun Ii Road Section Palembang City Using PKJI 2023 Method - Al Faritzie, Hariman; Misdalena, Felly; Aprilyanti, Selvia (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Sukabangun II Street in Palembang City is an area with a fairly high population density where the quantity of activities is quite high using vehicles on the road. The position of this road in Palembang City which is a traffic activity for the community's economy will affect street activities, especially at the intersection of this road. Traffic jams often occur due to narrowing of the road and slowing of vehicle flow along the intersection on Jalan R.A Abusamah and the direction of Jalan Beringin. This results in obstacles to traffic for people passing through Jalan Sukabangun II. In this study, an evaluation of the performance of the Sukabangun II road section in Palembang City was carried out. The method used is the PKJI 2023 method and is interpreted in 3-dimensional visualization using the PTV VISSIM Ver. 2021 microsimulation application. The results of the study showed a capacity value of 1,904 pcu units per hour, and a traffic flow value (Q) of 1160.8 pcu units per hour, so that the degree of saturation (DJ) was obtained as 0.61. This conclusion shows that the Sukabangun 2 road section in Palembang City is included in the category of roads with service level F.